INDICATORS OF FINANCING CIVIL SOCIETY INSTITUTIONS THROUGH STATE SUBSIDIES (International conference on multidisciplinary science, 2026)
Civil society institutions play a vital role in strengthening democratic governance, ensuring social justice, and delivering essential public services. In many countries, state subsidies constitute a primary mechanism for supporting the operational and project-based activities of non-governmental organizations (NGOs), foundations, public associations, and community groups. This article provides a comprehensive analysis of financial indicators used to evaluate state subsidy mechanisms for civil society institutions. It examines funding models, allocation criteria, efficiency metrics, transparency standards, and long-term sustainability challenges. The study also proposes recommendations for improving financial monitoring and accountability systems.